SISTEM BOARDING SCHOOL DI MASA PANDEMI DI MAN 1 SURAKARTA - Royyani NS, Mukhlis; Ali, Mohamad (Muhammadiyah University Press, 2020)
This research discusses the PANDEMIC Covid-19 which has changed many world orders, from economic, social to education. This study discusses the implementation of the system boarding school during the pandemic in MAN 1 Surakarta. This study aims to determine the implementation of the system boarding school during the pandemic in MAN 1 Surakarta and to identify the supporting and inhibiting factors of the system boarding school during the pandemic in MAN 1 Surakarta. This research uses field research with a survey research approach. The research subjects were wakakur madrasah, boarders boarding school, and students who took part in the program boarding school. Data collection techniques are interviews and documentation. Data analysis used data reduction, data presentation, and conclusion drawing. The results of this study indicate that the learning system used in the boarding school of MAN 1 Surakarta is virtual live streaming, assignments, and material giving. Meanwhile, the supporting factor of the system boarding school during this pandemic was in the form of madrasas facilitating wifi for tutors to support the online learning process, students got a free quote from the government, with online learning this could explain difficult and complicated learning materials to be easy and simple. While the inhibiting factors of the system boarding school during this pandemic were in the form of a lack of effectiveness and time efficiency due to students' parents who were busy working, unstable signals, and limited internet quotas made teachers and students in the online learning process not run optimally.